Effect of Different Mycorrhiza Treatments on Spore Counts in Oil Palm Topsoil - Shahidan, Syazwan; Rohaya Mohd Yusof; Noraini Ruslan; Mohamad Asyraf Hasli; Mohd Amirulhakim; Nadia Mohd Fadzli (Journal of Sustainable Natural Resources, 2023)
Mycorrhiza fungi are pivotal in oil palm cultivation, offering potential for enhanced growth and a reduced need for chemical fertilizers. However, the effectiveness of varying volumes and application timings of mycorrhiza remains an underexplored area. This gap, especially in the context of nursery-stage oil palm topsoil, challenges the advancement of sustainable cultivation practices. Addressing this, our study sought to evaluate the impact of different mycorrhiza volumes on spore counts in oil palm topsoil at nursery. Over a period of four months, we administered three levels of mycorrhiza treatments (0.5g, 1.0g, and 1.5g per plant) and conducted a thorough analysis using a 2-way ANOVA. The results revealed no statistically significant difference in spore counts due to varying mycorrhiza weights, as indicated by an F-value of 1.67 and a p-value of 0.209. However, the time factor, represented by different months, showed a significant impact on spore counts, with an F-value of 4.36 and a p-value of 0.014. Additionally, the interaction between mycorrhiza weight and month did not significantly influence spore counts, evidenced by an F-value of 0.31 and a p-value of 0.928. This study underscores the importance of temporal factors over mycorrhiza volume in oil palm nurseries and contributes valuable insights for optimizing sustainable cultivation practices.